Il "traffico delle lingue" Idiomi a contatto in Sardegna e nel Mediterraneo in età preunitaria - Fresu, Rita; Maninchedda, Paolo; Murgia, Giulia; Serra, Patrizia (Studi filologici e letterari, 2023)
This volume collects the results of the University of Cagliari's two-year research project "Trafficking between languages: idioms in contact in pre-unitary Sardinia," funded under the three-year agreement between the Fondazione di Sardegna and Sardinian Universities (Year 2020). The main objective of the research was to examine the linguistic contact between Sardinian, Italian and Castilian in the textual production of Sardinia, captured at the time of the transition from Iberian domination to Savoy rule. The synchronic chronological scope is identified mainly in the Sardinian eighteenth century, with some encroachment into the early nineteenth century, but the perspective framework rests on the cross-cultural and multilingual dynamics of the seventeenth century. The perimeter of investigation consists of a wide repertoire of texts written in Sardinian, Italian and Spanish, manuscript and printed, not only of a literary nature: it is a production as abundant and heterogeneous as ever, ranging from legal-administrative documentation to didactic literature, in which the new progressive spirit of the Enlightenment flows, up to treatises of a historiographic, lexicographic and historical-linguistic slant, in which reflection on the question of language takes shape.